2014
DOI: 10.1074/jbc.m113.539528
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Protein Complex, Pore Diameter, and Pore-forming Activity of the Borrelia burgdorferi P13 Porin

Abstract: Background: B. burgdorferi P13 has unique characteristics compared with other porins. Results: P13 is a homo-oligomer with a 0.6 nS conductance in 1 M KCl and a substrate cut-off of 400 Da. Conclusion: P13 represents a general diffusion pathway for small solutes into Borrelia. Significance: Understanding the molecular transport through P13 may play a role in designing more efficient antibiotic treatments against Borrelia infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The conductance of the toxin pores was investigated as a function of the hydrodynamic radii of different nonelectrolytes dissolved in the salt solution. These molecules have been used previously to determine the effective diameters of several channels reconstituted into planar lipid bilayers [40, 41, 6971]. Inspection of the results from nonelectrolytes suggested that the RtxA pore has a diameter of around 1.9 nm.…”
Section: Discussionmentioning
confidence: 99%
“…The conductance of the toxin pores was investigated as a function of the hydrodynamic radii of different nonelectrolytes dissolved in the salt solution. These molecules have been used previously to determine the effective diameters of several channels reconstituted into planar lipid bilayers [40, 41, 6971]. Inspection of the results from nonelectrolytes suggested that the RtxA pore has a diameter of around 1.9 nm.…”
Section: Discussionmentioning
confidence: 99%
“…At least four genes upregulated by c-di-GMP encode known or putative porins: DipA (encoded by bb0418) (92) and the three P13 paralogs (encoded by bbh41, bbi31, and bbq06) (93). P13 paralogs are thought to function as general diffusion porins, while DipA has a high affinity for dicarboxylates, including glutamate and pyruvate (92), which may help protect B. burgdorferi against oxidative damage within the fed midgut milieu.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the majority of the surface-exposed lipoproteins, all of the borrelial OMPs identified thus far are encoded on the ~900 kB linear chromosome [ 11 , 33 , 39 , 41 , 43 46 ]. While it is known that the borrelial OM contains membrane spanning OMPs with β-barrel structure and/or pore-forming capabilities that are important in overall physiology and host interactions, fewer than 10 borrelial proteins have been identified as potential OMPs and only half of those have thus far been characterized [ 22 , 33 , 39 , 41 , 45 52 ]. Of the known borrelial OMPs, B. burgdorferi proteins BamA (BB0795), BesC (BB0142), DipA (BB0418), P66 (BB0603), and P13 (BB0034) have been shown to form a β-barrel, to form pores in the borrelial OM, or to be functional orthologs to known OMPs.…”
Section: Introductionmentioning
confidence: 99%